Measuring the Effectiveness of Cooperative Ties in Knowledge Networks - Stejskal, Jan; Hájek, Petr (Academic Conferences and Publishing International, 2016)
Competitive advantage based on knowledge-intensive elements is often developed within innovation networks, strategic alliances, research centers, and consortia. Network-based operation among knowledge-intensive organizations helps to accelerate the pace of global technological change and helps diffuse complex knowledge and techniques at the international level. The interconnected actors cooperate and create an environment that promotes knowledge generation and transfer. Reciprocal willingness to share knowledge, trust, and even risk are important elements of a knowledge-intensive network's environment. This makes it possible to generate innovation – both faster and cheaper. The knowledge obtained, applied in the form of innovation, strengthens enterprise performance and increases an economy's competitiveness. Institutional support for research and development is carried out by various organizations in the Czech Republic. The Technology Agency of the Czech Republic (TACR) is the most important of these. It provides state support for applied research and experimental development. Its programs intentionally target cooperating stakeholders from the business and knowledge sectors. TACR supports projects that can reasonably expect to achieve various types of knowledge-intensive and commercializable results. Here, we constructed a knowledge network based on micro data from TACR concerning funding provided in the Pardubice region during the years 2011–2015. We focused on two primary industries in this region – the chemical and transportation industries. Using DEA analysis, we examined the effectiveness of TACR financial support, using project cost and the number of projects as inputs with patents and utility models being the multiple outputs. We show that cooperative ties in the chemical industry are more effective than in the transportation industry, which has important policy implications for state support of knowledge networks.
Měření efektivnosti kooperačních vazeb ve znalostních sítích
Keywords: Measuring; the; Effectiveness; Cooperative; Ties; Knowledge; Networks; Měření; efektivnosti; kooperačních; vazeb; znalostních; sítích